The ideal gas of hydrogen-like atoms response to the perturbation by the external electromagnetic field - Slyusarenko, Yu.V.; Sotnikov, A.G. (Вопросы атомной науки и техники, 2007)
The response of the ideal gas consisting of hydrogen-like atoms to the perturbation by the external electromagnetic field in low temperature region is studied. Consideration is based on using the Green functions formalism [1] and the second quantization method in the presence of bound states of particles [2]. As the most interesting phenomenon, the perturbation of system in Bose-condensation state is studied. The dispersion characteristics of such system at frequencies close to the energy interval between alkali atoms energy levels are investigated. Вивчено відгук ідеального газу, що складається із водневоподібних атомів, на збурення зовнішнім електромагнітним полем у низькотемпературній області. Дослідження базуються на використанні формалізму функцій Гріна [1] та методу вторинного квантування, що враховує можливість утворення зв’язаних станів частинок [2]. Як найбільш цікаве явище вивчено збурення системи, яка знаходиться у стані бозе-конденсації. Досліджені дисперсійні характеристики бозе-конденсату в області частот, близьких до інтервалів енергій між рівнями атомів лужних металів. Изучен отклик идеального газа, состоящего из водородоподобных атомов, на возмущение внешним электромагнитным полем в низкотемпературной области. Исследования основаны на формализме функций Грина [1] и методе вторичного квантования в присутствии связанных состояний частиц [2]. В качестве наиболее интересного явления изучено возмущение системы, находящейся в состоянии бозе-конденсации. Исследованы дисперсионные характеристики такой системы в области частот, близких к интервалам энергий между уровнями атомов щелочных металлов.